Introduction to Green Behaviour Through Video Media for Early Childhood in Firdausy Kindergarten, Sukoharjo - Giyatni, G; Katoningsih, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to educate young children on environmental conservation and foster green behaviors by introducing a video‐ based instructional session that raises awareness of maintaining a clean, balanced ecosystem and instills a sense of responsibility toward protecting the planet. Methodology: Using a qualitative case‐study approach, the research was conducted at Kindergarten Firdausy Sukoharjo. Data were gathered through classroom observations of the video session, semi‑structured interviews with teachers and children, and review of students’ post‑viewing reflections and creative activities designed to gauge their understanding and attitudes. Results: Following the video intervention, children demonstrated noticeably greater interest in environmental topics: they accurately identified ways to keep their surroundings clean, articulated simple conservation practices (e.g., waste separation, water saving), and willingly participated in group activities—such as planting seeds and picking up litter—reflecting a budding proactive stance toward green behavior. Applications/Originality/Value: By leveraging age‑appropriate video content, this study provides an effective model for early‑childhood educators to integrate environmental education into daily routines. Its findings offer practical guidance on designing multimedia lessons that cultivate sustainable attitudes from an early age, contributing to the broader field of ethnoscience‐informed pedagogy and supporting the development of lifelong eco‑responsible citizens.